Definition and Prospective Assessment of Functional Recovery After Liver Transplantation: A New Objective Consensus‐Based Metric for Safe Discharge. Issue 10 (25th August 2020) - Brustia, Raffaele; Boleslawski, Emmanuel; Monsel, Antoine; Barbier, Louise; Dharancy, Sébastien; Adam, René; Dumortier, Jérôme; Lesurtel, Mickaël; Conti, Filomena; Scatton, Olivier; ,
Abstract : Standardized discharge criteria are critical to reduce premature discharge and avoid unnecessary hospital stays. No such criteria exist for patients undergoing liver transplantation (LT). To achieve a consensus‐based checklist of criteria for safe patient discharge after LT, this mixed‐method study included the following: a systematic literature review and expert discussion to draft a first checklist of post‐LT discharge criteria, defining patient recovery and indications for hospital discharge (functional recovery); an exploratory online electronic Delphi (e‐Delphi) study; a single‐center pilot study to test checklist feasibility; and a final e‐Delphi study with an extended interdisciplinary expert panel to validate the final checklist. The first round provided a 10‐point discharge checklist with 5 patient‐centered items derived from discharge criteria after liver surgery and 5 graft‐centered items derived from expert discussion. The restricted panel (9 experts) e‐Delphi provided 100% consensus after the second round, with slight modifications to the criteria. During the pilot study, 19 of 45 (42.2%) patients included fulfilled the complete checklist (100% of 10 items) after median (IQR) 16 (8‐21) days (functional recovery) and a length of stay of 20 (9‐24) days. The item with the lowest completion rate was minimum serum tacrolimus level in the target on 2 consecutive blood samples (n = 21; 47%), achieved at 13 (9‐15) days. The extended panel (66 experts) e‐Delphi provided 95%‐98% consensus after the third round, with slight modifications of the criteria. This study provided substantial consensus on discharge criteria after LT. We anticipate that these criteria will be useful in clinical practice to guide patient discharge and increase the comparability of results between future studies.